(untitled) (International Journal of Food and Nutritional Sciences, 2022)
OCD is a very common mental illness that frequently manifests as an obsession with cleanliness, doubts, fear of harming oneself or others, religious, and sexual concerns. Eye movement desensitization and reprocessing (EMDR) therapy uses a standardized three-pronged method to address the past, present, and future aspects of a person’s traumatic memories. A fifth-grade student in an urban nuclear family aged 10 who has never had a history of psychiatric illness reported experiencing recurrent intrusive thoughts and witnessing his parents being fatally slashed. After speaking with the child’s mother, it was decided not to give the youngster any medication. At the beginning of treatment, the patient’s CYBOCS score was 24, which is regarded as severe. A score of two was obtained in the last session. EMDR therapy is well established to be an effective treatment for post-traumatic stress disorder, despite the lack of research on its usage for OCD.